JURIDICAL ANALYSIS OF THE CRIME OF ONLINE STORE FRAUD IN INDONESIA - Gazalba Saleh (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2022)
The growth of technology has increased the buying and selling of commodities virtually. However, the lack of physical stores makes it impossible for potential buyers to evaluate the quality of their commodities or facilities. This in turn encourages the emergence of virtual shopping scams by perpetrators. This paper mainly tries to evaluate the extent of online shopping fraud in Online Store Fraud Crimes in Indonesia by using a normative juridical approach, which uses secondary data. Fraud in cybercrime requires the victim to develop a statement of the actuality of the crime to police officers. The report must be accompanied by primary evidence in electrical information or methods of publication of electronic information and data. From there, to verify the actuality of a particular type of fraud, an investigation is carried out. The procedural law related to the ITE Law in Indonesia is regulated in article 42 which states that investigations into cybercrimes are carried out against the criminal procedure provisions in the ITE Law. Finally the essay finds that the Criminal Code of virtual fraud is regulated on Electronic Data and Transactions in Law number 19 of 2016.